Apelação no direito processual civil - Oliveira, Gleydson Kleber Lopes de (2005)
The appeal is an important resource in the scope of civil action that aims to impugn the decisive pronouncement entitled sentence. This study systemizes about the appeal in the civil procedural law, with the analysis of the multiple aspects related to the subject, under the light of legislation, doctrine and jurisprudence. The first part of this work copes with the sentence in the scope of judicial pronouncement. Its second part studies the appeal as a resource in the compared and previous Brazilian law, for then, examine the requirements of admission (suit, resourceful legitimacy, interest legitimacy, formal regularity, lack of extinctive or impeditive fact of the right to appeal, preparation and adhesion appeal), the effects (returnable, suspensive, transferable, substitute and regressive), and some polemic points (procedural nullity in a resourceful level, new questions and documents, chapters of the sentence, proof arrangements in a resourceful level, aggravation and not appealed sentence and anticipated guardianship in a resourceful level as well). Finally, the powers of the relator are analyzed, as well as the procedure in judgments of first and second instance, the trends of civil action, interpersonal law and the projects in process in the National Congress, proposing alteration of the CPC, from the appealing part